Influence of flicker characteristics on stroboscopic effects. (November 2016) - Bullough, JD; Marcus, D
This paper describes two human factors experiments designed to assess the influence of flicker characteristics on the perception of stroboscopic effects from flickering light. Specifically, the following factors were investigated: temporal waveform shape, frequency, duty cycle, percent flicker and flicker index. For a given frequency, the flicker index appears to be more predictive of the detection and acceptability of stroboscopic effects than the percent flicker value.